An Eastern Paradigm of Evaluation - Craig Russon (The Evaluation Center at Western Michigan University, 2008)
I recently taught a module on the philosophies of evaluation as part of a pilot introductory course of a new diploma programme jointly sponsored by the United Nations (UN) Evaluation Group and the United Nations Staff College (Russon, 2007, November). In the session, I compared and contrasted the "rationalistic" paradigm with the "naturalistic" paradigm on the basis of ontology, epistemology, and methodology.